A new species of the genus Cylindera (Coleoptera: Cicindelidae) from southern Bolivia with imitating behaviour to co-occurring ants - Šafránek, Ondřej; Amaya, Marcelo (Zootaxa, 2021)
Cylindera (Cylindera) julietae sp. nov. (Cicindelidae: Cicindelini) is described as new for science from southern Bolivia. The new species is compared to a similar species Cylindera (Cylindera) confluentesignata (W. Horn, 1915). Colour photographs of habitus, habitat and diagnostic characters of the two similar species are presented. The behaviour of adults of the new species, imitating that of co-occurring ants, is discussed.